2014
DOI: 10.1111/1755-0998.12262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of species in the angiosperm family Apiaceae using DNA barcodes

Abstract: Apiaceae (Umbelliferae) is a large angiosperm family that includes many medicinally important species. The ability to identify these species and their adulterants is important, yet difficult to do so because of their subtle fruit morphological differences and often lack of diagnostic features in preserved specimens. Moreover, dried roots are often the official medical organs, making visual identification to species almost impossible. DNA barcoding has been proposed as a powerful taxonomic tool for species iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 51 publications
(134 reference statements)
5
48
0
2
Order By: Relevance
“…In conclusion, we support the use of the ITS marker as a supplementary barcode in plants, while the performance of ITS should be evaluated in extensive trials in different plant groups (Liu et al, 2013; Liu J. et al, 2014; Wirta et al, 2016). The pragmatic solution to a complex trade-off between universality, sequence quality, discrimination, and cost, is the combination of T+I (90.5% species resolution), the most efficient and economical marker among single or combined DNA barcodes when identifying tree species in Aceraceae.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In conclusion, we support the use of the ITS marker as a supplementary barcode in plants, while the performance of ITS should be evaluated in extensive trials in different plant groups (Liu et al, 2013; Liu J. et al, 2014; Wirta et al, 2016). The pragmatic solution to a complex trade-off between universality, sequence quality, discrimination, and cost, is the combination of T+I (90.5% species resolution), the most efficient and economical marker among single or combined DNA barcodes when identifying tree species in Aceraceae.…”
Section: Discussionsupporting
confidence: 52%
“…In the past, biologists identified phylogenetic relationships and positions of biological specimens mainly based on morphological features, such as leaves, flower shape, size, and color. However, traditional taxonomy has at least two drawbacks: first, if the specimens are damaged or lack sufficient diagnostic characters, the specialists may be unable to make accurate identifications (Yan et al, 2015); second, morphologically and taxonomically difficult groups sometimes require an experienced professional taxonomist to address species identification (Li et al, 2011; Liu J. et al, 2014). Such taxonomists need training and experience, which require much time, effort and money.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ITS region was proposed as one of the core and powerful barcodes for seed plants (China Plant BOL Group, 2011), and its utility has also been supported in several barcoding studies (Liu et al, 2011, 2014; Muellner et al, 2011; Pang et al, 2011; Zhang et al, 2012; Chen et al, 2014; Zhang J. Q. et al, 2015). In a barcoding study of Euro-Mediterranean oaks, ITS2 increased the species resolution when combined with two plastid barcoding loci (Simeone et al, 2013); however, by itself, the ITS region showed no species identification when the genetic distance method was applied.…”
Section: Discussionmentioning
confidence: 99%
“…ITS is also useful as a species barcode for angiosperms , and adequate intraspecific and interspecific variation exists at this locus to delineate species within the family Apiaceae (Liu et al 2014). Although ITS has been useful at infrageneric-level analyses, it can also be effective in providing information about population genetic structure (e.g., Besnard et al 2007;Gao et al 2012;Lorenz-Lemke et al 2005).…”
Section: Management Implicationsmentioning
confidence: 99%